Bifidobacterium bifidum-Mediated Specific Delivery of Nanoparticles for Tumor Therapy - Tang Y (Dove Medical Press, 2021)
Yu Tang, Chun Chen, Binglei Jiang, Lu Wang, Fujie Jiang, Disen Wang, Yaotai Wang, Haiyan Yang, Xia Ou, Yan Du, Qi Wang, Jianzhong Zou State Key Laboratory of Ultrasound in Medicine and Engineering, Chongqing Key Laboratory of Biomedical Engineering, College of Biomedical Engineering, Chongqing Medical University, Chongqing, 400016, People’s Republic of ChinaCorrespondence: Jianzhong ZouState Key Laboratory of Ultrasound in Medicine and Engineering, Chongqing Key Laboratory of Biomedical Engineering, College of Biomedical Engineering, Chongqing Medical University, Chongqing, 400016, People’s Republic of ChinaTel +86-13708302390Email zoujzh@cqmu.edu.cnPurpose: Hypoxia is considered to be obstructive to tumor treatment, but the reduced oxygen surroundings provide a suitable habitat for Bifidobacterium bifidum (BF) to colonize. The anaerobe BF selectively colonizes into tumors following systemic injection due to its preference for the hypoxia in the tumor cores. Therefore, BF may be a potential targeting agent which could be used effectively in tumor treatment. We aimed to determine whether a novel BF-mediated strategy, that was designed to deliver AP-PFH/PLGA NPs (aptamers CCFM641-5-functionalized Perfluorohexane (PFH) loaded poly(lactic-co-glycolic acid) (PLGA) nanoparticles) by aptamer-directed approach into solid tumor based on the tumor-targeting ability of BF, could improve efficiency of high intensity focused ultrasound (HIFU) treatment of breast cancer.Methods: We synthesized AP-PFH/PLGA NPs using double emulsion method and carbodiimide method. Then, we evaluated targeting ability of AP-PFH/PLGA NPs to BF in vivo. Finally, we studied the efficacy of HIFU ablation based on BF plus AP-PFH/PLGA NPs (BF-mediated HIFU ablation) in tumor.Results: The elaborately designed AP-PFH/PLGA NPs can target BF colonized in tumor to achieve high tumor accumulation, which can significantly enhance HIFU therapeutic efficiency. We also found that, compared with traditional chemotherapy, this therapy not only inhibits tumor growth, but also significantly prolongs the survival time of mice. More importantly, this treatment strategy has no obvious side effects.Conclusion: We successfully established a novel therapy method, BF-mediated HIFU ablation, which provides an excellent platform for highly efficient and non-invasive therapy of tumor.Keywords: high intensity focused ultrasound, aptamers, nanoparticles, Bifidobacterium bifidum, tumor treatment